Orientación educativa y su incidencia en la vocación profesional en los estudiantes del tercer año de bachillerato en la especialización de contabilidad de la Unidad Educativa José María Velasco Ibarra, del Cantón el Empalme, año 2015 – 2016 - Arias Pincay, Paola Brigitte (2015)
Educational guidance in the vocational area determines the opportunities that are presented to students to choose their training, so that in practice it is expected that a young realistically choose engineering, and an aggressive, ambitious and verbal skills boy easily decide career studying law degree. If two or more directions have the same or almost the same strength, the individual hesitate in choosing an occupational environment. A girl with a combination of objective thoughts about problems with rejection of intimate relationships, with a tendency to organize combined with a desire to exercise self-control and a considerable tendency to be emotionally expressive, may one day choose to be a biologist and next day decide that for her the most suitable are the graphic arts. In examining the different scenarios that are presented to students they are the primary objective for the realization of this research work, considering that for this purpose there are parameters and important aspects to consider, such as the environment, family, peers and emotional inclination. For which the documentary and field research was used, as well as descriptive and explanatory research with inductive and deductive methods, covering a population that offers a sample of 66 teachers and 89 students involved in it. With results that show that the department of student counseling makes orientation talks and awareness to students, they do not cover the expectations and needs of the institution, when applying the test of a vocation, they are made circumstantially and without any preparation, guidance and pre-service training to ensure optimum results for their decision